2001
DOI: 10.1111/1469-7610.00772
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunctional Schemas and Cognitive Distortions in Psychopathology: A Test of the Specificity Hypothesis

Abstract: This study aimed at testing whether there were different types of dysfunctional schemas and cognitive distortions that could help to differentiate three emotional/behavioural problems, i.e., anxiety, depression, and aggression, from each other. Five hundred and eighty-one Chinese adolescents from five mainstream high schools in Hong Kong were recruited and completed several self-report questionnaires. Bivariate correlation showed an indiscriminate pattern of association between dysfunctional schemas, cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 25 publications
2
39
0
8
Order By: Relevance
“…The existing research on these cognitive errors using the Children's Negative Cognitive Error Questionnaire (CNCEQ; Leitenberg et al, 1986) suggests that they are associated with symptoms of anxiety and depression and that certain errors, such as catastrophizing and overgeneralizing, may be more related to anxiety, whereas selective abstraction may be more related to depression (Epkins, 1996;Leitenberg et al, 1986;Leung & Wong, 1998;Weems, Berman, Silverman, & Saavedra, 2001). However, as theoretically predicted by the cognitive content specificity hypothesis (Beck, 1976;Beck, Brown, Steer, Eidelson, & Riskind, 1987;Laurent & Stark, 1993), greater specificity has been obtained when the content of the cognitions are centered on depressive versus anxious content (Leung & Poon, 2001). Such findings suggest that it is not the type of bias per se that is specific to anxiety but the content of the bias (see also Laurent & Stark, 1993).…”
Section: Interpretive Biasesmentioning
confidence: 79%
“…The existing research on these cognitive errors using the Children's Negative Cognitive Error Questionnaire (CNCEQ; Leitenberg et al, 1986) suggests that they are associated with symptoms of anxiety and depression and that certain errors, such as catastrophizing and overgeneralizing, may be more related to anxiety, whereas selective abstraction may be more related to depression (Epkins, 1996;Leitenberg et al, 1986;Leung & Wong, 1998;Weems, Berman, Silverman, & Saavedra, 2001). However, as theoretically predicted by the cognitive content specificity hypothesis (Beck, 1976;Beck, Brown, Steer, Eidelson, & Riskind, 1987;Laurent & Stark, 1993), greater specificity has been obtained when the content of the cognitions are centered on depressive versus anxious content (Leung & Poon, 2001). Such findings suggest that it is not the type of bias per se that is specific to anxiety but the content of the bias (see also Laurent & Stark, 1993).…”
Section: Interpretive Biasesmentioning
confidence: 79%
“…To go a step further, Beck (1976) proposed that there are specific negative thoughts associated with either anxious or aggressive behaviors. Just as the predominant emotional reaction of fight/flight can be anger or fear (Carthy et al 2010a, b;Stadler et al 2006), the predominant anxious versus aggressive thoughts are often conceptualized as fear-or anger-related (Barrett et al 1996;Crick and Dodge 1994;Leung and Poon 2001;Schniering and Rapee 2002). Schniering and Rapee (2004) found evidence to support this theory in a sample of youth (7-16 years old).…”
Section: Content-specificitymentioning
confidence: 99%
“…There are also indications that early maladaptive schemas predict occupational stress [18]. Both early maladaptive schemas and cognitive distortions were found to be significantly associated with emotional problems, namely depression and anxiety [19]. In regards to cognitive distortions specifically, a study found that participants with depression showed strong negative interpretations of metaphors [20].…”
Section: Introductionmentioning
confidence: 99%